Position of Kazakhstan in International Trade and Business - Batyrkhanova, Yekaterina (2015)
This thesis presents an analysis of trends in world and foreign trade of Kazakhstan. It contains the main indicators characterizing the degree of product and geographic diversification of Kazakhstan's exports and imports. The thesis analyses the features, character and prospects of expansion of foreign economic relations of Kazakhstan, issues of strategic partnership, and trends shaping the model of the regional economy within the boundaries of the Eurasian Economic Space.